Modeling and analysis of the RI sensitivity of plasmonic sensor based on MIM waveguide-coupled structure. Issue 1 (March 2021) - Zegaar, I; Hocini, A; Ben salah, H
Abstract: In this paper, a plasmonic sensor is proposed based on a metal-insulator-metal waveguide coupled with a double-triangle resonator. The sensing structure is numerically and theoretically investigated using the two-dimensional finite difference time domain (FDTD) method. The results show the presence of a linear relationship between the materials refractive indices and the sensor's wavelength resonances. The proposed structure revealed a high sensitivity value, reaching the maximum value for mode 1 S mode1 = 1374 nm/RIU, and for mode 2 S mode2 = 2365 nm/RIU. The proposed sensor can be classified as a high-performance nano-sensor that can be used to identify different materials.